'The Father of the Experimental Philosophy of the Human Mind': Descartes and the Scottish Enlightenment's Moral Philosophers. Issue 3 (September 2022) - Calvente, Sofia
Abstract : Thomas Reid, Adam Ferguson and Dugald Stewart were exponents of the experimental philosophy of mind in the Scottish Enlightenment. The unique character of their philosophical project lies in the adoption of the mind-matter dualism as a necessary condition for the study of mental phenomena. This fact led them to recognize the importance of Descartes, both for being the first to clearly delimit the mental and material realms and for emphasizing the relevance of reflection as an instrument for the study of mind. But at the same time, the Frenchman was also the target of their criticism for dismissing the value of experimentation and appealing to hypotheses to explain natural behaviour. This paper aims to review this group of Scottish philosophers' views of the mind, explaining, at the same time, the reasons for their ambivalent attitude towards Descartes. In order to make sense of this ambivalence, I will argue that it is useful to bear in mind two different aspects of the methodology that the Scots put forward to study mental phenomena: firstly, the one between analogy and reflection and, secondly, the one between induction and hypothesis making.